2018
DOI: 10.1177/2168479017716717
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Reactions to Radiopharmaceuticals: A Survey Based on Clinical Cases Using Criteria of Systematic Review

Abstract: Adverse reactions to radiopharmaceuticals are still not reported worldwide. However, the type of reaction may be severe and cause death. A review of the literature was performed using some criteria of a systematic review established by the Cochrane Collaboration. The results showed that there are a large number of adverse reactions to radiopharmaceuticals. Nuclear medicine staff must be aware of the possibility of adverse reaction with radiopharmaceuticals and find time to share this information with the radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
2
5
0
2
Order By: Relevance
“…Our data showed that this was a single reported case of anaphylaxis in 6778 doses dispensed for administration. This low frequency of adverse events is in line with what is described in the literature [ 7 ]. Furthermore, there are not many studies on this subject.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data showed that this was a single reported case of anaphylaxis in 6778 doses dispensed for administration. This low frequency of adverse events is in line with what is described in the literature [ 7 ]. Furthermore, there are not many studies on this subject.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, there are not many studies on this subject. Nevertheless, adverse events with radiopharmaceuticals might be underreported [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The time delay of phosphonates radiopharmaceutical consistently reported could cause allergic reaction and another symptoms such as dermographism, nausea, malaise, vertigo, and pruritus. Those adverse reactions related to radiopharmaceuticals do occur and can be very severe [21].…”
Section: Resultsmentioning
confidence: 99%
“…Die Therapie von Skelettmetastasen, die Rezeptor-Liganden-Therapie oder die Radioimmuntherapie können ganz analog betrachtet werden. Passend zu den Ergebnissen der eigenen Risikoanalyse finden sich Berichte über Komplikationen bei der nuklearmedizinischen Therapie in der Literatur nur in Einzelfällen [28][29][30][31][32]. Für den Fall einer Ballonruptur bei der intravasalen Bestrahlung zur Prävention von Restenosen mit Re-188-Perrhenat wurde die nachträgliche Gabe von Perchlorat zur Reduktion der Strahlenexposition vorgeschlagen [33], jedoch wurde bislang kein entsprechender Fall berichtet.…”
Section: Nuklearmedizinische Therapieunclassified